Targeting Prostate Cancer Using Bispecific T-Cell Engagers against Prostate-Specific Membrane Antigen - Das, Gargi; Ptacek, Jakub; Havlinova, Barbora; Nedvedova, Jana; Barinka, Cyril; Novakova, Zora (ACS pharmacology & translational science, 2023)
Prostate cancer (PCa) tops the list of cancer-related deaths in men worldwide. Prostate-specific membrane antigen (PSMA) is currently the most prominent PCa biomarker, as its expression levels are robustly enhanced in advanced stages of PCa. As such, PSMA targeting is highly efficient in PCa imaging as well as therapy. For the latter, PSMA-positive tumors can be targeted directly by using small molecules or macromolecules with cytotoxic payloads or indirectly by engaging the immune system of the host. Here we describe the engineering, expression, purification, and biological characterization of bispecific T-cell engagers (BiTEs) that enable targeting PSMA-positive tumor cells by host T lymphocytes. To this end, we designed the 5D3-αCD3 BiTE as a fusion of single-chain fragments of PSMA-specific 5D3 and anti-CD3 antibodies. Detailed characterization of BiTE was performed by a combination of size-exclusion chromatography, differential scanning fluorimetry, and flow cytometry. Expressed in insect cells, BiTE was purified in monodisperse form and retained thermal stability of both functional parts and nanomolar affinity to respective antigens. 5D3-αCD3's efficiency and specificity were further evaluated in vitro using PCa-derived cell lines together with peripheral blood mononuclear cells isolated from human blood. Our data revealed that T-cells engaged via 5D3-αCD3 can efficiently eliminate tumor cells already at an 8 pM BiTE concentration in a highly specific manner. Overall, the data presented here demonstrate that the 5D3-αCD3 BiTE is a candidate molecule of high potential for further development of immunotherapeutic modalities for PCa treatment.